CCL4 as a potential serum factor in differential diagnosis of central nervous system inflammatory diseases and gliomas - Lyu, Tian-Jie; Wang, Jia; Zhao, Fengmao; Sun, Ke; Zhao, Zheng; Tian, Runfa; Guo, Zhendong; Wang, Haoran; Zhao, Xin; Ma, Wenping; Zhang, Mingshan; Xu, Wangshu (Frontiers in Immunology, 2024)
Computed tomography (CT) scans and magnetic resonance imaging (MRI) are commonly utilized to detect brain gliomas and central nervous system inflammation diseases. However, there are instances where depending solely on medical imaging for a precise diagnosis may result in unsuitable medications or treatments. Pathological analysis is regarded as the definitive method for diagnosing brain gliomas or central nervous system inflammation diseases. To achieve this, a craniotomy or stereotaxic biopsy is necessary to collect brain tissue, which can lead to complications such as cerebral hemorrhage, neurological deficits, cerebrospinal fluid leaks, cerebral edema, and others. Consequently, the advancement of non-invasive or minimally invasive diagnostic techniques is currently a high priority.